Neuroprotective Effect of Pentoxifylline on 3,4-Methylenedioxymethamphetamine-Induced Apoptosis in CA1 Cells of Wistar Rat Hippocampus: - Sharifi, Zahra Nadia; Movassaghi, Shabnam; Khazaei Koohpar, Zeinab; Hashemi, Mehrdad; Jafari Semnani, Sourena (Galen Medical Journal, 2019)
Background:Â 3,4-Methylenedioxymethamphetamine is psychoactive and hallucinogenic and has been shown to produce neurotoxicity both in animals and in humans. Recently, vasodilator drugs such as pentoxifylline (PTX) have been introduced as an alternative with neuroprotective effects. There is no study about the protective effect of PTX on hippocampal apoptosis due to high-dose administration of 3,4-Methylenedioxymethamphetamine (MDMA), so in this study, the protective effect of PTX on the hippocampus of male Wistar rats following high-dose of the drug has been investigated. Materials and Methods: Twenty-four male Wistar rats weighing 250-300 g were randomly divided into four groups: control, sham (MDMA injection), experimental (MDMA+PTX injection), and vehicle (MDMA+saline) groups. Two weeks later, the brains were removed and prepared for TUNEL and western blot techniques. Concomitantly the hippocampus was removed to study the change in Bcl-2 and BAX mRNA expression with quantitative real-time polymerase chain reaction. Results: Data showed that the number of apoptotic bodies significantly decreased in the experimental group compared to the other groups, except for in control. Also, further investigation revealed that BAX reduced considerably, while Bcl-2 mRNA expression increased dramatically after PTX treatment. Conclusions: Our results suggest that PTX may be a neuroprotective agent, and its neuroprotective potential may contribute to reducing the severity of lesions in the hippocampus following a high dose administration of MDMA. [GMJ.2019;8:e963]Â 